Effects of 16-week tai chi practice on sit-to-stand performance and lower-limb neuromuscular control strategies in community-dwelling older adults: a randomized controlled trial - Mozhu, Lyu; Jiayu, Li (Frontiers in Physiology, 2025)
BackgroundThe ability to perform sit-to-stand (STS) transitions is a fundamental marker of functional independence in older adults, and age-related declines in STS performance are strongly linked to increased fall risk and compromised quality of life. While mind–body exercises like Tai Chi have shown promise in enhancing physical function in this population, the specific neuromuscular mechanisms through which Tai Chi improves STS performance—particularly how it modulates biomechanical patterns and muscle control during this critical movement—remain poorly understood.ObjectiveThis study aimed to investigate the effects of a 16-week, Yang-style Tai Chi programme on STS performance and lower limb neuromuscular control strategies underpinning any improvements in older adults. Methods: Sixty community-dwelling older adults (60–75 years) stratified by sex and baseline STS time. The 32 older adults were recruited as the experimental group (Tai Chi practitioners), and 28 as the control group (maintaining habitual lifestyle). The experimental group underwent 16 weeks of Tai Chi practice (5 sessions/week, 40 min/session), while the control group maintained their original daily routines. Before and after the intervention, the following parameters were measured during STS transitions: center of pressure (COP), temporal parameters, and surface electromyography (sEMG) signals of relevant lower limb muscles.ResultsData indicated that with increasing age, older adults exhibited decreased physical activity levels and impaired STS ability. After 16 weeks of Tai Chi practice, the experimental group showed significant improvements in STS ability, with marked reductions in reaction time, standing phase duration, and total time for Five Times Sit-to-Stand Test (FTSST). During STS tasks, the sample entropy of COP in the experimental group significantly decreased, accompanied by reduced sEMG amplitudes of the biceps femoris, rectus femoris, and tibialis anterior.ConclusionThis study demonstrated that aging is associated with declines in physical activity, reaction capacity, and STS ability in older adults. Tai Chi improves STS performance through greater neuromuscular efficiency and reduced postural sway, providing a mechanistic rationale for its integration into fall-prevention programs for older adults.